Solid electrolyte membrane, solid electrolyte membrane-negative electrode integrated structure, preparation method and battery
By using large metal radius MOF materials and surfactants to prepare solid electrolytes, and fit the activated surface of activated lithium foil, the problem of poor contact with positive and negative pole and low ionic conductivity in solid batteries has been solved. Higher battery cycle stability and ion conductivity.
Patent Information
- Application Number
- CN202411657016.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The electrolyte stability and flammability of traditional lithium-ion batteries lead to low safety, and poor contact between solid electrolyte and positive and negative electrodes and low ionic conductance lead to the hindering of the development of solid-state batteries.
The method of combining the combination of MOF materials and surfactants is used to prepare solid electrolytes and fit the activated surface of the activated lithium foil to form an integrated structure of solid electrolyte-negative electrode.
Improve the ionic conductivity of the solid electrolyte, improve the interface contact between the solid electrolyte and the negative electrode, and enhance the cycle stability of the battery and the ionic conductivity.
Smart Images

Figure CN119381580A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a solid electrolyte membrane and an integrated structure of a solid electrolyte membrane-anode. Background Art
[0002] Lithium-ion batteries have received great attention from the business and scientific communities due to their high energy density and high power density. However, the stability and flammability of traditional lithium-ion battery electrolytes lead to low safety of lithium-ion batteries, which seriously affects the commercial development of lithium-ion batteries. Solid-state batteries are high-safety batteries that use solid electrolytes as the transmission medium for positive and negative electrodes, but the poor contact between solid electrolytes and positive and negative electrodes and low ionic conductivity have hindered the development of solid-state batteries. Summary of the invention
[0003] In view of the problems existing in the prior art, the object of the present invention is to provide a solid electrolyte membrane and a preparation method thereof, as well as a solid electrolyte membrane-negative electrode integrated structure and a preparation method thereof.
[0004] To achieve the above objectives, the present invention provides the following specific technical solutions.
[0005] First, the present invention provides a method for preparing a solid electrolyte membrane, comprising the following steps: Mixing a large metal radius MOF material, a surfactant I, and a solvent I to obtain a slurry A; Drying slurry A to obtain a solid phase; grinding the solid phase to obtain a modified MOF material; The modified MOF material, lithium salt, polymer and solvent II are mixed to obtain slurry B; After the slurry B is formed into a film, a solid electrolyte membrane is obtained.
[0006] In a further preferred embodiment, the large metal radius MOF material is at least one of MOF-808, MOF-801, PCN-128, PCN-223, and MIP-202.
[0007] In a further preferred embodiment, the surfactant I is at least one of dodecyltrimethylammonium bromide, n-octyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, and sodium dodecyl sulfate.
[0008] In a further preferred embodiment, the solvent I is one or both of methanol and ethanol.
[0009] In a further preferred embodiment, in slurry A, the content of large metal radius MOF material is 0.8-2.0 g / L; the content of surfactant I is 0.5-1.2 wt % of the large metal radius MOF material.
[0010] In a further preferred embodiment, the drying method is water bath heating drying, and the water bath heating temperature is further preferably 70-80°C.
[0011] In a further preferred embodiment, the lithium salt is at least one of LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethylsulfonyl)imide), LiBF4, LiPF6, LiNO3, and LiClO4.
[0012] In a further preferred embodiment, the polymer is at least one of PVDF (polyvinylidene fluoride), PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene), and PVDF-CTFE (polyvinylidene fluoride-chlorotrifluoroethylene).
[0013] In a further preferred embodiment, the solvent II is one or both of DMF (N,N-dimethylformamide) and NMP (N-methylpyrrolidone).
[0014] In a further preferred embodiment, in slurry B, the concentration of the polymer is 90-120 g / L; the concentration of the lithium salt is 7-100 g / L; and the mass of the modified MOF material is 40-80% of the mass of the polymer.
[0015] Based on the same inventive concept, the present invention provides a solid electrolyte membrane prepared by the above preparation method.
[0016] Secondly, the present invention provides a method for preparing an integrated structure of a solid electrolyte membrane-negative electrode, comprising the following steps: A mixed solution containing surfactant II and hydrofluoric acid is sprayed on the surface of the lithium foil, and after drying, an activated lithium foil is obtained; The aforementioned solid electrolyte membrane is laminated to the activated surface of the activated lithium foil to obtain an integrated structure of the solid electrolyte membrane-negative electrode.
[0017] In a further preferred embodiment, in the mixed solution, the content of surfactant II is 0.08-0.15 g / L; the content of hydrofluoric acid is 0.008-0.015 g / L.
[0018] In a further preferred embodiment, the solvent of the mixed solution is at least one of methanol and ethanol.
[0019] In a further preferred embodiment, the amount of the mixed solution sprayed on the surface of the lithium foil is 1-3 μL / cm 2 .
[0020] Based on the same inventive concept, the present invention provides an integrated structure of a solid electrolyte membrane-negative electrode prepared by the above preparation method.
[0021] Furthermore, the present invention provides a battery comprising the aforementioned solid electrolyte membrane-negative electrode integrated structure.
[0022] The above one or more technical solutions of the present invention can achieve at least one of the following beneficial effects: The preparation method of the solid electrolyte membrane provided by the present invention improves the ion conductivity of the solid electrolyte membrane, thereby obtaining a solid electrolyte membrane with excellent ion conductivity.
[0023] The solid electrolyte membrane-negative electrode integrated structure provided by the present invention has good interface contact between the solid electrolyte membrane and the negative electrode, thereby reducing the problem of poor battery capacity stability caused by polarization and limited contact area.
[0024] The solid electrolyte membrane-negative electrode integrated structure provided by the present invention can improve the cycle stability and ion conductivity of the battery.
[0025] The preparation method provided by the invention has simple process, strong controllability and can be applied on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The cycle performance curves of the batteries assembled with the integrated structure obtained in Examples 5 to 8 are shown.
[0027] Figure 2 The cycle performance curves of the batteries assembled with the integrated structures obtained from Comparative Examples 5-1 to 5-5 are shown.
[0028] Figure 3 LSV curves of the Li-SS symmetric batteries assembled with an integrated structure obtained in Examples 5 to 8.
[0029] Figure 4 LSV curves of the Li-SS symmetric batteries assembled with the integrated structures obtained in Comparative Examples 5-1 to 5-5. DETAILED DESCRIPTION
[0030] In a first aspect, some embodiments of the present invention provide a method for preparing a solid electrolyte membrane, comprising the following steps: Mixing a large metal radius MOF material, a surfactant I, and a solvent I to obtain a slurry A; Drying slurry A to obtain a solid phase; grinding the solid phase to obtain a modified MOF material; The modified MOF material, lithium salt, polymer and solvent II are mixed to obtain slurry B; After the slurry B is formed into a film, a solid electrolyte membrane is obtained.
[0031] In order to increase the ionic conductivity of the polymer solid electrolyte, a large metal radius MOF material is introduced. At the same time, surfactant I is introduced to increase the dispersibility of the large metal MOF material and to form a surfactant coating on the surface of the large metal radius MOF material, thereby further increasing the ionic conductivity of the large metal radius MOF material.
[0032] MOF materials are coordination compounds with a crystal structure formed by metal ions and ligands. Metal ions with larger radii will form larger gaps during the coordination process. Combined with the unique long-range ordered lattice structure of MOF materials, they have a significant effect on improving the conductivity of lithium ions.
[0033] Surfactants have strong binding sites for lithium ions, which is one of the prerequisites for lithium ion transport. In addition, surfactants can be evenly dispersed on the surface of particles, which increases the ion active sites on the surface of particles on the one hand and increases the ion exchange between particles on the other hand.
[0034] In some specific embodiments, the large metal radius MOF material is at least one of MOF-808, MOF-801, PCN-128, PCN-223, and MIP-202, and more preferably MOF-808.
[0035] In some specific embodiments, the surfactant I is at least one of dodecyltrimethylammonium bromide, n-octyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, and sodium dodecyl sulfate, and is more preferably dodecyltrimethylammonium bromide.
[0036] In some specific embodiments, the solvent I is one or both of methanol and ethanol.
[0037] In some specific embodiments, the content of the large metal radius MOF material in slurry A is 0.8-2.0 g / L; the content of surfactant I is 0.5-1.2% of the large metal radius MOF material. If the content of surfactant I is too little, uniform coating may not be formed; if the content of surfactant I is too much, interference from impurity cations may occur.
[0038] In some specific embodiments, the drying method is water bath heating drying, and it is further preferred that the water bath heating temperature is 70-80° C. Of course, those skilled in the art may also choose other conventional drying methods in the art, such as oven drying.
[0039] In some specific embodiments, the lithium salt is at least one of LiFSI, LiTFSI, LiBF4, LiPF6, LiNO3, and LiClO4, more preferably LiFSI. Those skilled in the art may also select other conventional lithium salts in the field of electrolytes in the art.
[0040] In some specific embodiments, the polymer is at least one of PVDF, PVDF-HFP, and PVDF-CTFE.
[0041] In some specific embodiments, the solvent II is one or both of DMF and NMP.
[0042] In some specific embodiments, in slurry B, the concentration of the polymer is 90-120 g / L; the concentration of the lithium salt is 7-100 g / L; and the mass of the modified MOF material is 40-80% of the mass of the polymer.
[0043] In a second aspect, some embodiments of the present invention provide a solid electrolyte membrane prepared by the above-mentioned preparation method.
[0044] In a third aspect, some embodiments of the present invention provide a method for preparing an integrated structure of a solid electrolyte membrane-anode, comprising the following steps: A mixed solution containing surfactant II and hydrofluoric acid is sprayed on the surface of the lithium foil, and after drying, an activated lithium foil is obtained; The aforementioned solid electrolyte membrane is laminated to the activated surface of the activated lithium foil to obtain an integrated structure of the solid electrolyte membrane-negative electrode.
[0045] The surface sprayed with the mixed solution is the activated surface of the activated lithium foil. The lithium foil is reacted with hydrofluoric acid to form a lithium compound, and an artificial SEI film similar to the SEI film is formed on the surface of the lithium foil. In the process of generating the artificial SEI film, the surfactant participates in the reaction to form an SEI film with surfactant components, so that the components in the artificial SEI film and the solid electrolyte are similar, which is beneficial to increase the contact between the solid electrolyte and the negative electrode interface and increase the cross-linking between molecules. Good contact has a good effect on the cycle stability of the battery, including the ion transport at the interface, and can reduce the problem of poor battery capacity stability caused by polarization and limited contact area.
[0046] The SEI film is a thin film formed at the negative electrode interface due to side reactions that is conductive to ions but not to electrons. The thickness may be only a dozen nanometers to micrometers, which is generally thin, which means that the amount of surfactant and hydrofluoric acid used is very small. However, if the amount is too small, the reaction is not sufficient, the composition of the SEI film becomes uncontrollable, and the too thin SEI film does not provide good protection for the negative electrode material; if the amount is too large, the reaction is too violent, which is not conducive to the uniformity and gas production of the film, and the film is too thick, which is not conducive to the ion conduction of the battery, and too many side reactions are generated, and the loss of active substances is also large. After multiple experimental verifications, in some specific embodiments, in the mixed solution, the content of surfactant II is 0.08~0.15g / L; the content of hydrofluoric acid is 0.008~0.015g / L.
[0047] In some specific embodiments, the amount of the mixed solution sprayed on the surface of the lithium foil is 1-3 μL / cm 2 .
[0048] In addition, some embodiments of the present invention provide an integrated structure of a solid electrolyte membrane-negative electrode prepared by the above preparation method, and provide a battery comprising the above integrated structure of a solid electrolyte membrane-negative electrode.
[0049] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0050] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0051] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0052] Example 1 (1) 1.0 g MOF808 and 0.01 g dodecyltrimethylammonium bromide were added to 1000 ml methanol and mixed thoroughly to obtain solution A. Solution A was then stirred and dried at 75 °C and ground thoroughly to obtain a modified MOF material. (2) Take 0.5 g of the modified MOF material obtained in step (1), 0.8 g of LiFSI, and 1.0 g of PVDF-HFP, add them into 10 mL of NMP and mix thoroughly to obtain solution B, then pour solution B onto a flat glass plate and dry it to obtain a solid electrolyte membrane.
[0053] Comparative Example 1-1 0.5 g of MOF808 material, 0.8 g of LiFSI, and 1.0 g of PVDF-HFP were added to 10 mL of NMP and mixed thoroughly to obtain solution B, which was then poured onto a flat glass plate and dried to obtain a solid electrolyte membrane.
[0054] Comparative Example 1-2 0.8 g of LiFSI and 1.0 g of PVDF-HFP were added to 10 mL of NMP and mixed thoroughly to obtain a solution B, which was then poured onto a flat glass plate and dried to obtain a solid electrolyte membrane.
[0055] Example 2 (1) 2.0 g MOF-801 and 0.024 g sodium dodecylbenzene sulfonate were added to 1000 ml ethanol and mixed thoroughly to obtain solution A. Solution A was then stirred and dried at 80° C. and ground thoroughly to obtain a modified MOF material. (2) 0.96 g of the modified MOF material obtained in step (1), 1.0 g of LiFSI, and 1.2 g of PVDF were added to 10 mL of NMP and mixed thoroughly to obtain solution B. Solution B was then poured onto a flat glass plate and dried to obtain a modified solid electrolyte.
[0056] Example 3 (1) 0.8 g PCN128 and 0.004 g n-octyltrimethylammonium bromide were added to 1000 ml methanol and mixed thoroughly to obtain solution A. Solution A was then stirred and dried at 70 °C and ground thoroughly to obtain a modified MOF material. (2) Take 0.5 g of the modified MOF material obtained in step (1), 0.8 g of LiPF6, and 1.0 g of PVDF-HFP, add them into 10 mL of DMF and mix thoroughly to obtain solution B, then pour solution B onto a flat glass plate and dry it to obtain a modified solid electrolyte.
[0057] Example 4 (1) 1.0 g of MIP-202 and 0.01 g of sodium dodecyl sulfate were added to 1000 ml of methanol and mixed thoroughly to obtain solution A. Solution A was then stirred and dried at 75 °C and ground thoroughly to obtain a modified MOF material. (2) Take 0.4 g of the modified MOF material obtained in step (1), 0.8 g of LiFSI, and 1.0 g of PVDF-CTFE, add them into 10 mL of NMP and mix thoroughly to obtain solution B, then pour solution B onto a flat glass plate and dry it to obtain a modified solid electrolyte.
[0058] Example 5 Prepare a methanol solution with a concentration of 0.1 g / L dodecyl trimethyl ammonium bromide and 0.01 g / L hydrofluoric acid, and spray 2 μL / cm on the surface of the lithium foil. 2 solution to obtain activated lithium foil.
[0059] The activated surface of the activated lithium foil was bonded to the solid electrolyte membrane obtained in Example 1 to obtain an integrated structure.
[0060] Comparative Example 5-1 The difference between Comparative Example 5-1 and Example 5 is that the activated surface of the activated lithium foil is laminated to the solid electrolyte membrane obtained in Comparative Example 1-1 to obtain an integrated structure.
[0061] Comparative Example 5-2 The difference between Comparative Example 5-2 and Example 5 is that the activated surface of the activated lithium foil is laminated to the solid electrolyte membrane obtained in Comparative Example 1-2 to obtain an integrated structure.
[0062] Comparative Example 5-3 Spray 2 μL / cm on the surface of lithium foil 2 A methanol solution of hydrofluoric acid with a concentration of 0.01 g / L was prepared to obtain activated lithium foil.
[0063] The activated surface of the activated lithium foil was bonded to the solid electrolyte membrane obtained in Example 1 to obtain an integrated structure.
[0064] Comparative Example 5-4 2 μL / cm2 of a methanol solution of dodecyltrimethylammonium bromide with a concentration of 0.1 g / L was sprayed on the surface of the lithium foil to obtain an activated lithium foil.
[0065] The activated surface of the activated lithium foil was bonded to the solid electrolyte membrane obtained in Example 1 to obtain an integrated structure.
[0066] Comparative Example 5-5 The lithium foil (not activated) was laminated to the solid electrolyte membrane obtained in Example 1 to obtain an integrated structure.
[0067] Example 6 Prepare an ethanol solution with a concentration of 0.08 g / L of n-octyltrimethylammonium bromide and a concentration of 0.012 g / L of hydrofluoric acid, and spray 3 μL / cm on the surface of the lithium foil. 2 solution to obtain activated lithium foil.
[0068] The activated surface of the activated lithium foil was bonded to the solid electrolyte membrane obtained in Example 2 to obtain an integrated structure.
[0069] Example 7 Prepare an ethanol solution with a concentration of 0.15 g / L dodecyl trimethyl ammonium bromide and 0.015 g / L hydrofluoric acid, and spray 1 μL / cm on the surface of the lithium foil. 2 solution to obtain activated lithium foil.
[0070] The activated surface of the activated lithium foil was bonded to the solid electrolyte membrane obtained in Example 3 to obtain an integrated structure.
[0071] Example 8 Prepare a methanol solution with a concentration of 0.1 g / L dodecyl trimethyl ammonium bromide and 0.008 g / L hydrofluoric acid, and spray 2 μL / cm on the surface of the lithium foil. 2 solution to obtain activated lithium foil.
[0072] The activated surface of the activated lithium foil was bonded to the solid electrolyte membrane obtained in Example 4 to obtain an integrated structure.
[0073] The integrated structures obtained in Example 5-8 and Comparative Examples 5-1 to 5-5 were respectively assembled into batteries in the following manner: The integrated structures were cut into discs with a diameter of 16 mm to serve as the negative electrode and electrolyte of the battery. The commercial six-series (622) ternary positive electrode material was mixed with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as a solvent. The mixture was placed in a small beaker and stirred at a speed of 800 r / min for 2 hours to obtain a slurry. Use an automatic coating machine to coat the slurry on the current collector aluminum foil, place it flat on tempered glass and transfer it to a vacuum drying oven at 85°C for 4 hours. After punching out into pole pieces with a diameter of 12 mm, dry them in a vacuum drying oven at 105°C for 4 hours, place them in a glove box filled with argon atmosphere with a water and oxygen content of less than 0.1 ppm for 4 hours to reduce the moisture adsorbed by the pole pieces during the transfer process, and then assemble them into CR2032 button batteries in the glove box.
[0074] After the battery is assembled and aged for 12 hours, a charge and discharge test is performed: 100 cycles at a voltage of 2.8-4.3V and 1.0C.
[0075] The integrated structures obtained in Example 5-8 and Comparative Examples 5-1 to 5-5 were respectively assembled into Li-SS symmetrical batteries in the following manner: the integrated structure was cut into a disc with a diameter of 16 mm to serve as the negative electrode and solid electrolyte of the battery, and then a stainless steel sheet with a diameter of 16 mm was placed as the positive electrode on the other side of the solid electrolyte membrane, and a spring was added to equip a CR2032 button battery in a glove box. The battery was left at room temperature for 6 hours, and an LSV test was performed on an electrochemical workstation, and a scan speed of 1 mV / s was set to scan from 2V to 6V, and the change state of the current was observed to determine the change of voltage and current.
[0076] The charge and discharge test results are as follows: Figure 1 and Figure 2As shown. As can be seen from the figure, the capacity of the battery assembled with the integrated structure obtained in Examples 5 to 8 after 100 cycles is 151.9 mAh / g, 166.9 mAh / g, 165.9 mAh / g, and 165.4 mAh / g, respectively, and the capacity of the battery assembled with the integrated structure obtained in Comparative Examples 5-1, 5-2, 5-3, 5-4, and 5-5 after 100 cycles is 9.5 mAh / g, 97.9 mAh / g, 99.0 mAh / g, 92.7 mAh / g, and 36.2 mAh / g, respectively. Obviously, the integrated structure of the solid electrolyte membrane-negative electrode proposed in the present invention makes the battery cycle performance better. This may be based on the directional selection of large metal radius MOF materials and the combined effect of surfactants in the electrolyte and the interface, which plays a role in stabilizing the interface and reducing side reactions. In addition, by comparing the cycle performance of the battery assembled with the integrated structure obtained in Example 5 and Comparative Example 5-1, it can be seen that when no surfactant is added to the solid electrolyte membrane, the improvement effect on the cycle performance of the battery is poor; by comparing the cycle performance of the battery assembled with the integrated structure obtained in Example 5 and Comparative Example 5-5, it can be seen that simply optimizing the solid electrolyte membrane may not provide a significant improvement in the stable cycle performance of the battery.
[0077] LSV test results are as follows Figure 3 and Figure 4 As shown. It can be seen from the figure that the voltage windows of the Li-ss symmetrical batteries assembled with the integrated structure obtained in Examples 5 to 8 are 4.80V, 4.78V, 4.29V, and 4.83V, respectively, and the voltage windows of the Li-ss symmetrical batteries assembled with the integrated structure obtained in Comparative Examples 5-1, 5-2, 5-3, 5-4, and 5-5 are 4.22, 3.95, 3.68, 4.45, and 3.30V, respectively. In other words, the integrated structure of the solid electrolyte membrane-negative electrode provided by the present invention enables the battery to have significantly higher voltage stability. This is mainly based on the combined effect of the large metal radius MOF material and the surfactant in the solid electrolyte, which pushes up the physicochemical properties of the organic polymer material; in addition, the modification of the lithium metal side also reduces the generation of by-products and reduces the toxic effect of by-products on the solid electrolyte, which is also an important factor in improving the interface stability.
[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a solid electrolyte membrane, characterized in that: The following steps are involved: Mixing a large metal radius MOF material, a surfactant I, and a solvent I to obtain a slurry A; Drying slurry A to obtain a solid phase; grinding the solid phase to obtain a modified MOF material; The modified MOF material, lithium salt, polymer and solvent II are mixed to obtain slurry B; After the slurry B is formed into a film, a solid electrolyte membrane is obtained.
2. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The large metal radius MOF material is at least one of MOF-808, MOF-801, PCN-128, PCN-223, and MIP-202; the surfactant I is at least one of dodecyltrimethylammonium bromide, n-octyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, and sodium dodecyl sulfate; and the solvent I is one or both of methanol and ethanol.
3. The method for preparing a solid electrolyte membrane according to claim 1 or 2, characterized in that: In slurry A, the content of large metal radius MOF material is 0.8~2.0g / L; the content of surfactant I is 0.5~1.2wt% of the large metal radius MOF material.
4. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The lithium salt is at least one of LiFSI, LiTFSI, LiBF4, LiPF6, LiNO3, and LiClO4; the polymer is at least one of PVDF, PVDF-HFP, and PVDF-CTFE; and the solvent II is one or both of DMF and NMP.
5. The method for preparing a solid electrolyte membrane according to claim 1 or 4, characterized in that: In slurry B, the concentration of the polymer is 90~120g / L; the concentration of the lithium salt is 7~100g / L; and the mass of the modified MOF material is 40~80% of the mass of the polymer.
6. A solid electrolyte membrane, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 5.
7. A method for preparing an integrated structure of a solid electrolyte membrane-negative electrode, characterized in that: The following steps are involved: A mixed solution containing surfactant II and hydrofluoric acid is sprayed on the surface of the lithium foil, and after drying, an activated lithium foil is obtained; The solid electrolyte membrane according to claim 6 is laminated to the activated surface of the activated lithium foil to obtain an integrated structure of the solid electrolyte membrane-negative electrode.
8. The method for preparing the integrated structure of solid electrolyte membrane-negative electrode according to claim 7, characterized in that: In the mixed solution, the content of surfactant II is 0.08-0.15 g / L; the content of hydrofluoric acid is 0.008-0.015 g / L; the solvent of the mixed solution is at least one of methanol and ethanol; the amount of the mixed solution sprayed on the surface of the lithium foil is 1-3 μL / cm 2 .
9. A solid electrolyte membrane-negative electrode integrated structure, characterized in that: It is prepared by the preparation method according to claim 7 or 8.
10. A battery, characterized in that: An integrated structure comprising the solid electrolyte-negative electrode as described in claim 9.
Citation Information
Patent Citations
MOFs-based solid electrolyte membrane and preparation and application thereof
CN114725507A
Multi-layer composite electrolyte membrane based on metal-organic framework material and preparation method of multi-layer composite electrolyte membrane
CN115458807A
MOFs-based solid polymer electrolyte as well as preparation method and application thereof
CN117558973A
Pre-oxidized and vulcanized MOF-based lithium ion battery solid electrolyte and preparation method thereof
CN118398876A
Lithium ion battery solid electrolyte with positive and negative electrode interface modification and preparation method of lithium ion battery solid electrolyte
CN118412528A